The Use of Illness Narratives in Undergraduate Physiotherapy, Medicine, and Nutrition: Innovative Experiences at a University in São Paulo (Global Journal of Human-Social Science, 1970)
With the purpose of consolidating the implementation of the National Curriculum Guidelines in the health area an innovative project involving higher courses in Physiotherapy Medicine and Nutrition was conceived at a University located in the city of S o Paulo This qualitative research brings the perceptions of the participating students about the project regarding the analysis of the content of reflective portfolios and transcripts of conversation circles carried out after the collection of illness narratives by those undergraduates The students were able to reflect on themes such as the multidimensionality of falling ill comprehensive care the need to incorporate psychosocial aspects for the person s understanding how much emotions are a factor in the illness experience and the need to broaden the perspective of such process This activity is considered to have brought important reflections to those undergraduates towards the achievement of the current guidelines contributing to a more humanistic and interdisciplinary approach in such professions
Keywords: higher education curriculum humanization of assistance